THU0236 Undifferentiated connective tissue disease: outcome of 40 patients. (1st June 2001) - Romero, M; Aguirre, MA; Cisnal, A; Font, P; Cuadrado, MJ; Martinez, FG; Gonzalez, J; Escudero, A; Perez, V; Castro, C; Muñoz-Villanueva, MC; Collantes, E
Abstract : Background: There are a substantial number of patients with symptoms strongly suggestive of a connective tissue disease (CTD) that does not adequately fulfil enough classification criteria to be labelled as such. The outcome of these patients is difficult to predict. They are classified as undifferentiated connective tissue disease (UCTD). Objectives: To prospectively analyse the outcome of a cohort of patients with UCTD. Methods: Patients with 2 clinical criteria plus 1 serological criteria or 2 serological plus 1 clinical criteria for the classification of any CTD were included. A protocol including clinical and serological parameters was completed at entry in the study and, thereafter, annually. The end point of the study was for the patient to have met enough classification criteria to be labelled as a defined CTD. Results: Forty patients with UCTD (37 women and 3 men, mean age 43 ± 15 years and mean follow-up 3.43 ± 2.5 years) were included. During the follow-up, 13 patients fulfilled criteria for a defined CTD (32.5%): 6 fulfilled criteria for rheumatoid arthritis, 4 for systemic lupus erythematosus, 2 for systemic sclerosis and 1 for Sjogren`s syndrome. Sixteen patients still remained unclassified (40%) and 11 patients (27.5%) were completely asymptomatic. There was no association between clinical or serological parameters and outcome. Conclusion: After a mean follow-up of 3.5 years, one third of the UCTD patients evolved into a defined CTD. We found no clinical or serological factors to predict outcome.